Organização da produção agropecuária e integração ao setor urbano-industrial: um estudo de caso - Vilas Boas, Ana Alice (1992)
This study had as aims to characterize the farming unities (FUs) of Itirapua village through a set of varianbles which tries: to describe the process of production organization within these FUs and the process by which they are aggregated into industrial-urban sector; to analyse the production cost and to stablish relantionships between kinds of farming unities and economical profit: identifying, according to the producers' perception placed in different categories of FUs, the problems faced with, their origins and possible solutions. It was adopted in this work, the tabular analysis method to classify the FUs, the theoretical classical model of cost calculation to identify the economical situations of these farming unities and the content analysis technique of the to diagnosticate the problems faced by the producers. The twenty farming unities studied were classified into five social-economical categories through the multi dimensional procedure. The basic variants indicated that the FUs differentiate concerning the income level, commercialization level, value of the investiment, prevailing labour force and development of off-farming activities. The complementary variables and the descriptive variables of the rural-urban integating process contributed to the description of the profile of the identified categories. The study has dernonstrated that the economic situations was differentiated, within a same category, which suggest that new studies should be carried out in order to relate economical profit with classification of the producers. This study has also showm that the perception which the producers had of the reality in which they live in, allied to the characterization of FUs and identification of the economical situation of FUs provided to the agencies of rural extension elements to formulate differentiated and suitable strategies with the needs and desires of the title-holders of the different kinds farming unities in a same rural locality. In synthesis, this study has led to a global diagnosis of the farming unities, because besides analysing the enterprise aspect has analysed the social aspect which directly or indirectly affects the performance of the FUs. Thus, when one works in this perspective one contributes to the development of the rural management, because one notices that the inner environment of the FU is a reflection of the transformations occurred in the society as a whole.